Constantly Changing: Revitalization of Our Existing Building Stock with a User-centric Approach Through the Comparison of Three Hungarian Examples - Szuszik, Dóra (International Journal of Engineering and Management Sciences, 2023)
Our built environment’s community-oriented spaces are rapidly becoming obsolete in response to current social, cultural and economic demands. The renovation project of the tímárház Szárító műhely in Debrecen presents a new potentional transformation model in the region with a focus on community-creating and cultural awareness. The incremental, cost-effective small-scale intervention and adaptive reuse of the building’s spaces provide an opportunity to preserve its values and swiftly respond to evolving needs. In order to validate the underlying principles of the interventions proposed in the plan, it will be compared to two similar-minded examples, the Művészeti Ellátó in Eger and Szabadkikötő in Pécs. The projects were examined through the processes occuring within their respective life cycles, as their transformations exhibit recurring patterns. The analyses were conducted based on interviews with the creators, online articles, studies and on-site visits.